Atmospheric Spray Freeze Drying of Sugar Solution With Phage D29 - Ly, Alvin; Carrigy, Nicholas B.; Wang, Hui; Harrison, Melissa; Sauvageau, Dominic; Martin, Andrew R.; Vehring, Reinhard; Finlay, Warren H. (Frontiers in Microbiology, 2019)
Therapeutic bacteriophages offer a potential alternative approach in the treatment of drug resistant bacteria. In the present study, we examine the ability of atmospheric spray freeze-drying to process bacteriophage D29 into a solid dry formulation. Bacteriophage D29 is of particular interest due to its infection of Mycobacterium tuberculosis. A sugar solution containing bacteriophage D29 was sprayed and instantly frozen in a cold chamber. Cold drying gas was then passed through the chamber at a high flow rate and atmospheric pressure. Convective transport combined with the low temperature of the drying gas results in sublimation of ice, yielding a free-flowing, porous powder. The bacteriophages were atmospheric spray freeze-dried in solutions with varying concentrations of trehalose and mannitol. A solution of trehalose and mannitol at a mass ratio of 7:3 and a total mass concentration of 100 mg/mL led to powder with 4.9 ± 0.1 % moisture content and an acceptable titer reduction of ~0.6 logs. In comparison, a pure trehalose solution and a 1:1 ratio of trehalose and mannitol both had titer reductions of >1.5 logs. Spectroscopic analysis showed that trehalose in the powder was amorphous while mannitol completely crystallized, both of which are desirable for preserving phage viability in powders. The results highlight the potential for using atmospheric spray freeze-drying as an alternative process in preserving biopharmaceutical products.